Narratives Crossing Borders The Dynamics of Cultural Interaction - Jansson, Bo G.; Jonsson, Herbert; Berg, Lovisa; Edfeldt, Chatarina (Stockholm Studies in Culture and Aesthetics, 2021)
Which is the identity of a traveler who is constantly on the move between cultures and languages? What happens with stories when they are transmitted from one place to another, when they are retold, remade, translated and re-translated? What happens with the scholars themselves, when they try to grapple with the kaleidoscopic diversity of human expression in a constantly changing world? These and related questions are, if not given a definite answer, explored in the chapters of this anthology. Its overall topic, narratives that pass over national, language and ethnical borders include studies about transcultural novels, poetry, drama and the narratives of journalism. There is a broad geographic diversity, not only in the anthology as a whole, but also in each of the single contributions. This in turn demand a multitude of theoretical and methodological approaches, which cover a spectrum of concepts from such different sources as post-colonial studies, linguistics, religion, aesthetics, art and media studies, often going beyond the well-known Western frameworks. The works of authors like Miriam Toews, Yoko Tawada, Javier Moreno, Leila Abouela, Marguerite Duras, Kyoko Mori, Francesca Duranti, Donato Ndongo-Bidyogo, Rībi Hideo, and François Cheng are studied from a variety of perspectives. Other chapters deal with code-switching in West-african novels, border-crossing in the Japanese noh drama, translational anthologies of Italian literature, urban legends on the US-Mexico border, migration in German children's books, and war trauma in poetry. Most of the chapters are case studies, and may thus be of interest, not only for specialists, but also for the general reader.